INVENTARISASI TUMBUHAN PAKU (PTERIDOPHYTA) DI KAWASAN KAMPUS IAIN PALANGKA RAYA SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN MATERI KLASIFIKASI TUMBUHAN - Ayatusa'adah Ayatusa'adah; Nor Apriyani Dewi (Edu Sains: Jurnal Pendidikan Sains dan Matematika)
The purpose of this research is to have an inventory on Fern-plants in the area of IAIN Palangka Raya as an alternative media to discuss or learn about the classification of plants for high school students. The method applied was qualitative research through survey activities to have an inventory on fern-plants. In collecting the data, the procedure was done by tracking the ferns growing area and collecting every kind of ferns species found in IAIN Palangka Raya. Identification of ferns species were using the key of determination. The data of the research were analyzed descriptively to get connected with the development of alternative learning media. The inventory result has been